Pengaruh Penggunaan Media Pembelajaran Berbasis Virtual Laboratorium Dan LKS Interaktif Terhadap Minat Belajar Siswa Pada Materi Momentum Dan Impuls - Rike Dwi Wulandari; Putri Wihatma Andianti; Ratna Sary Anindy; Jazilatul Mufida; Maryani Maryani (Peneliti.net, 2023)
Learning media is an important component that must exist in every learning process takes place. The use of instructional media greatly influences student interest and learning outcomes, besides that the use of instructional media also influences student learning motivation. This research method uses a quantitative approach with an appropriate research design. The research sample consisted of class XI high school students. Data collection was carried out using a questionnaire as a research instrument, specifically designed to measure the level of student interest in the material and student perceptions regarding the use of virtual laboratory-based learning media and interactive worksheets. By going through the validation and reliability tests, the result is that the student learning interest questionnaire is valid. The results of the study concluded that appropriate, interactive and interesting learning media can increase students' interest in learning, especially in exact subjects such as Physics. By increasing student learning interest, student learning outcomes will also increase, as well as the level of student completeness will also increase